Analisis Bibliometrik: Perkembangan Penelitian Green Accounting dalam Mendukung Bisnis Berkelanjutan - Putri, Mega Amalia; Yuliana, Yuliana; Maulana, Haikal Zulian; Royani, Asri (Jurnal KIAFE, 2024)
This study maps the development of green accounting research in supporting sustainable business during the 2013–2023 period. Publication data were retrieved from Google Scholar using the Publish or Perish application, resulting in 928 documents. The study employs a bibliometric analysis supported by VOSviewer to examine publication trends, citation patterns, keyword co-occurrence, research clusters, and emerging topics. The results show that publications on green accounting generally increased during the observation period and reached their highest level in 2022. The keyword network formed seven research clusters, with green accounting emerging as the most dominant topic. Related themes include corporate social responsibility, environmental accounting, environmental disclosure, environmental performance, financial performance, profitability, and sustainable development. Environmental information appears as a relatively underexplored topic with weak network connections to green accounting. This finding indicates an opportunity for future studies to examine the relationship between green accounting implementation and environmental information disclosure. Overall, effective green accounting practices can support sustainable business by integrating environmental costs, economic benefits, and environmental protection into organizational decision-making.